Applying critical discursive psychology to health psychology research: a practical guide. Issue 1 (1st January 2020) - Locke, Abigail; Budds, Kirsty
ABSTRACT: This paper outlines a qualitative methodological approach called Critical Discursive Psychology (CDP), considering its applicability to health psychology research. As applied to health psychology, the growth of discursive methodologies within the discipline tends to be located within a critical health psychology approach where CDP and others enable a consideration of how wider societal discourses shape understandings and experiences of health and illness. Despite the increasing usage of CDP as a methodology, little has been written on the practical application of the method to date, with papers instead focusing on the theoretical underpinnings of a CDP approach. This paper seeks to address that gap and offers a step by step guide to the key principles and analytic stages of CDP before giving a worked example of CDP applied to a health topic, in this case 'baby-led weaning' (BLW). As we discuss, a key strength of CDP, particularly in relation to health psychology, is in its attempts to understand both macro and micro levels of data analysis. By doing so it offers a nuanced and richer understanding of how particular health topics are working within context. Therefore, CDP is a readily applicable analytic approach to contested and complicated topic areas within health research.